Outcome in patients with diffuse large B-cell lymphoma who relapse after autologous stem cell transplantation and receive active therapy: a retrospective analysis of the Lymphoma Working Party of the European Society for Blood and Marrow Transplantation (EBMT) - González Barca, Eva; Dreger, Peter (Bone marrow transplantation, 2020)
Autologous hematopoietic stem cell transplantation (auto-HSCT) is the standard of care for patients with diffuse large B-cell lymphoma (DLBCL) who relapse/progress after first line chemoimmunotherapy. Long-term outcome of those who relapse after transplant is poor. We present the results of a retrospective study of 256 adult patients reported to the EBMT registry with DLBCL who relapsed after auto-HSCT performed between 2003 and 2013, and who received active salvage strategies. One hundred and fifty-four (60%) were male; median age was 53 years. Median time to relapse was 7 months, 65% relapsed during the first year. Overall response rate after salvage therapy was 46%. Median follow-up after first salvage therapy was 40 months (IQR 23-63 months). Overall survival (OS) at 3 years was 27% (95% CI 22-33). OS at 3 years of patients relapsing longer than 1 year after auto-HSCT was 41% (95% CI 31-53) compared with 20% (95% CI 14-24) in those who relapsed in less than 1 year. Eighty-two patients (32%) had a second HSCT, an allogeneic HSCT (allo-HSCT) in 69 cases, at a median time of 6.5 months after relapse. OS at 3 years after allo-HSCT was 36% (95% CI 25-51). In conclusion, the prognosis of patients with DLBCL that relapse after auto-HSCT is dismal. Patients who relapse in less than 1 year remain an unmet need, and should be considered for CAR T cell therapy or clinical trials. Patients who relapse after 1 year can be rescued with salvage therapies and a second HSCT. These results provide a benchmark to compare data of new prospective studies.
Published online: 20 September 2019
Gesehen am 12.03.2020